Review Artikel: Pengaruh Penggunaan Vitamin C Pada Pasien Covid - 19 - Gita Kurniawati Putri; Indah Laily Hilmi; Salman Salman (Journal of Pharmaceutical and Sciences, 2023)
Coronavirus, or COVID-19, is a virus that causes disease in animals or humans. The spread of this virus is thought to be carried out by bats and other animals that humans eat. The immunity of Covid-19 patients is significant because it speeds up the healing process. Vitamin C is a water-soluble nutrient and vitamin that is essential for life and health. Vitamin C is also known by the chemical name ascorbic acid. This literature study aims to determine the use of vitamin C in the treatment of COVID-19 patients. The method used is a systematic literature review by collecting several journals on vitamin C treatment in COVID-19 patients. The results obtained showed that the administration of vitamin C is beneficial in the healing process of COVID-19 patients both intravenously and orally.